K KOMBINASI EKSTRAK DAUN LIDAH BUAYA (Aloe vera L.) DAN DAUN SIRIH (Piper betle L.) TERHADAP DAYA HAMBAT Pseudomonas aeruginosa SECARA IN VITROKOMBINASI EKSTRAK DAUN LIDAH BUAYA (Aloe vera L.) DAN DAUN SIRIH (Piper betle L.) TERHADAP DAYA HAMBAT Pseudomonas - -, Rahmawati; Kurnia Risna, Yayuk; Nuraida (Program Studi Magister Pengelolaan Sumberdaya Alam dan Lingkungan Universitas Almuslim, 2023)
Research has been carried out in the Laboratory of mathematics and natural sciences, almuslim university. The study aims to determine the interaction between concentration and type of leaf Aloe vera L extract to inhibition Pseudomonas aeruginosa. The research method was experimental method. The antibacterial activity assays performed using the diffusion method. The research used Randomized Completely Design (RCD) factorial and three replications. Variables measured were diameter of inhibition formed and color characteristics diameter inhibition. Data were analyzed using analysis of varian (ANOVA), followed by Duncan's test. The results showed there are interaction between the concentration and type of extract Aloe vera L. leaf and Piper betel L leaves to the inhibition of Pseudomonas aeruginosa. The greater concentration of extract, the greater inhibition zone made.Research has been carried out in the Laboratory of mathematics and natural sciences, almuslim university. The study aims to determine the interaction between concentration and type of leaf Aloe vera L extract to inhibition Pseudomonas aeruginosa. The research method was experimental method. The antibacterial activity assays performed using the diffusion method. The research used Randomized Completely Design (RCD) factorial and three replications. Variables measured were diameter of inhibition formed and color characteristics diameter inhibition. Data were analyzed using analysis of varian (ANOVA), followed by Duncan's test. The results showed there are interaction between the concentration and type of extract Aloe vera L. leaf and Piper betel L leaves to the inhibition of Pseudomonas aeruginosa. The greater concentration of extract, the greater inhibition zone made.Research has been carried out in the Laboratory of mathematics and natural sciences, almuslim university. The study aims to determine the interaction between concentration and type of leaf Aloe vera L extract to inhibition Pseudomonas aeruginosa. The research method was experimental method. The antibacterial activity assays performed using the diffusion method. The research used Randomized Completely Design (RCD) factorial and three replications. Variables measured were diameter of inhibition formed and color characteristics diameter inhibition. Data were analyzed using analysis of varian (ANOVA), followed by Duncan's test. The results showed there are interaction between the concentration and type of extract Aloe vera L. leaf and Piper betel L leaves to the inhibition of Pseudomonas aeruginosa. The greater concentration of extract, the greater inhibition zone made.Research has been carried out in the Laboratory of mathematics and natural sciences, almuslim university. The study aims to determine the interaction between concentration and type of leaf Aloe vera L extract to inhibition Pseudomonas aeruginosa. The research method was experimental method. The antibacterial activity assays performed using the diffusion method. The research used Randomized Completely Design (RCD) factorial and three replications. Variables measured were diameter of inhibition formed and color characteristics diameter inhibition. Data were analyzed using analysis of varian (ANOVA), followed by Duncan's test. The results showed there are interaction between the concentration and type of extract Aloe vera L. leaf and Piper betel L leaves to the inhibition of Pseudomonas aeruginosa. The greater concentration of extract, the greater inhibition zone made.Research has been carried out in the Laboratory of mathematics and natural sciences, almuslim university. The study aims to determine the interaction between concentration and type of leaf Aloe vera L extract to inhibition Pseudomonas aeruginosa. The research method was experimental method. The antibacterial activity assays performed using the diffusion method. The research used Randomized Completely Design (RCD) factorial and three replications. Variables measured were diameter of inhibition formed and color characteristics diameter inhibition. Data were analyzed using analysis of varian (ANOVA), followed by Duncan's test. The results showed there are interaction between the concentration and type of extract Aloe vera L. leaf and Piper betel L leaves to the inhibition of Pseudomonas aeruginosa. The greater concentration of extract, the greater inhibition zone made.Research has been carried out in the Laboratory of mathematics and natural sciences, almuslim university. The study aims to determine the interaction between concentration and type of leaf Aloe vera L extract to inhibition Pseudomonas aeruginosa. The research method was experimental method. The antibacterial activity assays performed using the diffusion method. The research used Randomized Completely Design (RCD) factorial and three replications. Variables measured were diameter of inhibition formed and color characteristics diameter inhibition. Data were analyzed using analysis of varian (ANOVA), followed by Duncan's test. The results showed there are interaction between the concentration and type of extract Aloe vera L. leaf and Piper betel L leaves to the inhibition of Pseudomonas aeruginosa. The greater concentration of extract, the greater inhibition zone made.